Clean soups : simple, nourishing recipes for health and vitality - Katz, Rebecca; Edelson, Mat (Ten Speed Press, 2016)
"Soup has a unique ability to nourish and heal the body. In Clean Soups, author Rebecca Katz shows you how to use wholesome stocks and soups to naturally detox and stay energized year-round. She also explains the building blocks for creating deliciously balanced soups, such as Moroccan carrot soup, kale soup with coconut and lime, and simplest chicken pho. With foundational broths, blended soups, and traditional healing soups, as well as a two-day cleanse, Clean Soups shows how one simple bowl can make a huge difference in how you feel,"--Amazon.com.